Extraction and Activity Test of Antibacterial Compounds from Limberry Leaves (Triphasia Trifolia) Against Vibrio Sp. - Novita Herdiana; Yosua Musada Sagala; Samsul Rizal; Maria Erna Kustyawati (Pandawa Institute, 2025)
Limberry (Triphasia trifolia) is one of traditional medicinal plants whereas its leaves are known for various uses, one of which is as an antibacterial agent. The most common bacteria found in marine waters is Vibrio sp. This work seeks to distinguish antibacterial compounds inside the ethanol extract of limberry leaves and assess its repressive effect on Vibrio sp. The research was conducted with three repetitions and five different concentration levels: D1 (5%), D2 (10%), D3 (15%), D4 (20%), and D5 (25%). The observational data were analyzed using a completely randomized design (CRD) analysis of variance, followed by the least significant difference (LSD) test at a 5% significance level. Phytochemical screening revealed that the ethanol extract of limberry leaves contained antibacterial compounds namely flavonoids, tannins, steroids, alkaloids, and phenolics. UV-Vis spectrophotometry analysis indicated that the ethanol extract of limberry leaves had absorption at wavelengths of 202, 211, 228, 253, 270, and 323 nm. FTIR analysis showed that the ethanol extract of limberry leaves contained some functional groups, i.e., O–H, C–H alkanes, C–H alkenes C≡N, C=O, C=C, C–O esters, and C–O ethers. The inhibitory test also demonstrated that the ethanol extract of limberry leaves could inhibit the growth of Vibrio sp., with inhibition zone diameters formed at each concentration of 5%, 10%, 15%, 20%, and 25% being 7.280, 7.640, 7.713, 8.027, and 8.070 mm, respectively.